Rancangan Aplikasi Pengelolaan Event, Pemesanan E-Tiket dan E-Sertifikat di Politeknik Negeri Sriwijaya - Widia Salsabila; Ahmad Taqwa; Lindawati Lindawati (Universitas Budi Darma, 2022)
State Polytechnic of Sriwijaya currently uses the conventional method of distributing information, such as posting event pamphlets on campus bulletin boards. However, this method has proven ineffective because many students rarely see the bulletin boards, resulting in some failing to register for events because they are unaware of them. In addition, the procedure for registering event participants is still inefficient, as participants' information is handwritten on the registration form paper, which might result in the paper being lost or damaged. Then, the event certificate issuing system still in physical form will necessitate a lengthier issue procedure. Therefore, an event management system must be created to facilitate the distribution of information about upcoming events at the State Polytechnic of Sriwijaya. This system also incorporates ticket purchasing and certificate issuance using Android and the Laravel website, allowing for more efficient event ticket purchase and issuing electronic certificates (e-certificates). The prototype method is used in the application development method and the Unified Modeling Language (UML) system was used in the system design phase, while MySQL was employed as the database. This study reveals that the designed application system can efficiently support the online distribution of information, ticket purchasing, and issuance of electronic certificates. The findings of system testing via the blackbox method demonstrate that all of the designed application system's features operate correctly and effectively. From the results of the UAT test, this system is included in the very feasible category. Supported by the results of software testing of each factor: variable functionality 96.2% (very feasible), variable Efficiency 97.2% (very feasible), variable Usability 96.2% (very feasible).